2016
DOI: 10.1007/s12687-016-0271-7
|View full text |Cite
|
Sign up to set email alerts
|

Counsellee’s experience of cancer genetic counselling with pedigrees that automatically incorporate genealogical and cancer database information

Abstract: While pedigree drawing software is often utilised in genetic services, the use of genealogical databases in genetic counselling is unusual. This is mainly because of the unavailability of such databases in most countries. Electronically generated pedigrees used for cancer genetic counselling in Iceland create pedigrees that automatically incorporate information from a large, comprehensive genealogy database and nationwide cancer registry. The aim of this descriptive qualitative study was to explore counsellees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…GHPs have previously raised concerns that asking consent to use information for relatives might create anxiety or prevent sharing (Dheensa et al, , , 2018Forbes Shepherd et al, 2017). However, similar to our findings, previous studies have found that patients want to know how information could be used, and understanding how information is protected might be important for patient reassurance and trust Diergaarde et al, 2007;Horton & Lucassen, 2019;Stefansdottir et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…GHPs have previously raised concerns that asking consent to use information for relatives might create anxiety or prevent sharing (Dheensa et al, , , 2018Forbes Shepherd et al, 2017). However, similar to our findings, previous studies have found that patients want to know how information could be used, and understanding how information is protected might be important for patient reassurance and trust Diergaarde et al, 2007;Horton & Lucassen, 2019;Stefansdottir et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…for other clinical genetics patient cohorts in the United Kingdom and Iceland, who appreciated the benefits of family genetic information, but had privacy concerns, and wanted to know how information was used Stefansdottir et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platforms from published papers [28,[30][31][32][33][34][35] and Google [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] were identified and evaluated. A set of criteria (Supplementary Table S1) was adapted for evaluating platforms [51].…”
Section: Aofg Platformmentioning
confidence: 99%